Peripheral line for vasopressor administration: Prospective multicenter observational cohort study for survival and safety - Adane Petros; Addisu Melkie; Kehabtimer Shiferaw Kotiso; Dawit Kebede; Chala Fekadu Oljira; Fitsum Assefa Gemechu; Hanan Yusuf; Sintayehu Abebe; Aschalew Ashagre; Amsalu Bekele; Andargew Yohannes; Eyob Kebede Etesa; et al. (PLoS ONE, 2025)
Background The placement of a central venous catheter (CVC) is associated with a high risk of central line-related bacteremia and mechanical complications. In a resource-constrained environment, the use of CVC is limited as a result of the complexity of the procedure and the need for a trained expert to place it. There is scant evidence on the feasibility, outcome, and safety of administering vasopressors using a peripheral venous catheter (PVC). Hence, our study, which is the first of its kind, evaluated the survival outcome, predictors, and safety of vasoactive drug administration via peripheral intravenous access in patients with circulatory shock. Methods A prospective cohort study was conducted in the Emergency Department and ICU setting of selected public and private hospitals in Addis Ababa on selected 250 circulatory shock patients over 6 months for whom vasopressor was administered peripherally. Data was collected daily using ODK by study site coordinators and trained data collectors. Statistical analysis was done using STATA 14.1 using descriptive analysis, Kaplan Meir survival analysis, and cox regression analysis. Results The median (IQR) age of the participants was 48.5 (35, 62). From circulatory shock causes, septic and cardiogenic shock accounted for 69.6% and 22.0% respectively. There were 3 extravasation injuries from the 250 patients that occurred exclusively on patients that took vasopressor for more than 4 days yielding an event rate of 1.2% and 0.004/patient day. Mortality in circulatory shock patients is high with a 57.6% mortality rate in general and 67.8% in septic shock patients. A Cox regression analysis identified decreased baseline systolic blood pressure [AHR = 0.98; 95%CI: 0.95, 0.99], decreased urine output [AHR = 0.96; 95%CI: 0.93, 0.99], septic shock compared to cardiogenic shock [AHR = 0.48; 95%CI: 0.24, 0.94], and use vasopressor other than norepinephrine [AHR = 0.6; 95%CI: 0.39, 0.92] as independent predictors of death of circulatory shock patients with peripherally administered vasopressors. Conclusion Our study found that peripheral venous catheter use for vasopressor administration in circulatory shock was associated with a low extravasation rate (1.2%), with all events occurring after more than five days, indicating it might be a safe alternative to CVC for short-term use in resource-limited settings. Findings support cautious prolonged use and consideration of central access when therapy exceeds a few days. This calls for randomized controlled trials to compare the safety and efficacy of vasopressor administration by PVC versus CVC.